PEMANFAATAN MEDIA SOSIAL INSTAGRAM UNTUK MENINGKATKAN PROMOSI DAN NILAI JUAL PRODUK UMKM TAS DI KOTA BOGOR - Hurriyaturrohman, Hurriyaturrohman; Maulani, Denia (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
The purpose of this research is to find out the Small and Medium Micro, Small and Medium Enterprises (MSMEs) of Bogor City Bags in Utilizing Instagram social media as a promotional medium and increasing the selling value of their products. The method used is descriptive qualitative research by means of field observations, in-depth interviews, and documentation. The results show that Instagram social media has many features, which are frequently used, namely the IG Story feature, DM (direct message), highlight, promote / boost ost / ads. Besides Instagram, it also has an E-Commerce account like shopee. Meanwhile, to proceed to the product order stage, you can go through the Whatsapp application, shopee. So the role of Instagram as a media for product promotion at UMKM Bags in Bogor City is very important and has a big effect on the economy of MSME owners. What’s more, the use of Instagram is considered cheaper and more efficient than other media. Social media Instagram can increase the sales of Bogor City MSME Bag products especially with the Covid-19 pandemic conditions which require people to stay at home and shopping centers are closed. Keywords: Instagram, Promotion, MSME, Sales